Außenansicht des Iwalewahaus (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright exclusively held by Georgina Beier Estate Executor, or jointly by Iwalewahaus, CBCIU. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Art; Painting; Africa; Exhibitions; Artists; Art Exhibition; Iwalewahaus; Cultural Centre; Performing Arts Center; Art Collector; Art Collecting